2004
DOI: 10.1002/j.2048-7940.2004.tb00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Positioning, Wheelchair Seating, and Pulmonary Function of Children with Cerebral Palsy: A Research Synthesis

Abstract: This review analyzed research literature concerning pulmonary function and positioning of persons with cerebral palsy (CP) who lack trunk control. The search reviewed literature published from 1966 through March 2003. Twenty-eight references located by electronic database search were analyzed using Moody's Research Analysis Tool. All reflected either a physiologic or therapy-based model involving function in activities of daily living, but no health outcomes. One reference applied a nursing model to care of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Significant improvement in pulmonary functions (VC, FEV 1 , PEF) revealed in meta-analysis may be related to increased respiratory muscle strength from training [9]. Previous studies [30,31] reported that the increase in VC of the spastic CP children can be attributed to the better control of breathing through elimination of the abnormal breathing patterns and strengthening of the respiratory muscles. It is possible that the respiratory training is important to counterbalance the natural decline of pulmonary functions in these patients.…”
Section: Discussionmentioning
confidence: 87%
“…Significant improvement in pulmonary functions (VC, FEV 1 , PEF) revealed in meta-analysis may be related to increased respiratory muscle strength from training [9]. Previous studies [30,31] reported that the increase in VC of the spastic CP children can be attributed to the better control of breathing through elimination of the abnormal breathing patterns and strengthening of the respiratory muscles. It is possible that the respiratory training is important to counterbalance the natural decline of pulmonary functions in these patients.…”
Section: Discussionmentioning
confidence: 87%
“…Without trunk control, the paraspinal extensors and abdominal muscles cannot provide balanced co-contraction to hold the trunk upright. Gravity pulls downward, resulting in the collapse of the trunk into scoliosis or rotoscoliosis (Barks, 2004). The depth of the thoracic support of the IF decreased significantly compared with that of the AAF.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral palsy is the term for a range of non-progressive syndromes of posture and motor impairment that results from an insult to the developing central nervous system (Koman et al, 2004). People with cerebral palsy who have not developed trunk control have difficulty eating, speaking, moving about, and executing regular activities associated with daily living (Barks, 2004). Patients with cerebral palsy are often prescribed special seating systems for use in their wheelchairs for the purposes of improving posture and to help prevent the development of long-term deformity.…”
Section: ) Department Of Health Sciences Hokkaido University Schoolmentioning
confidence: 99%
“…Otherwise, chest wall development is impaired ( 77 ). Children who cannot sit unsupported cannot co-contract paraspinal and abdominal muscles, resulting in immediate mid-trunk collapse and slumped posture ( 78 ), and evolving into fixed kyphoscoliosis over time ( Figure 2 ). Malalignment of the spine from any cause contributes to reduced gas exchange (hypoxemia and hypercapnia), increased resistive load to breathing, and increased risk of upper airway obstruction (UAO), atelectasis, and pneumonia caused by unequal expansion of lungs ( 29 , 79 ).…”
Section: Risk Factors For Respiratory Illnessmentioning
confidence: 99%